Identifikasi Penerapan Konsep Kota Hijau di Kota Banda Aceh berdasarkan Kategori Asian Green City Index - Ridha Ulfa Sukma; Mirza Irwansyah; Myna Agustina Yusuf (Jurnal RAUT, 2023)
The city of Banda Aceh has been involved in implementing the green city concept through the green city development program from 2011 to 2015. In 2012, the city of Banda Aceh completed the preparation of the green open space master plan document and the green city action plan document. This study aims to examine the implementation of the eight green city categories carried out in Banda Aceh City after participating in the green city development program based on the Asian Green City Index (AGCI). The method in this study used a qualitative descriptive method based on the results of observations and interviews as well as literature studies. The results of this study indicate that the application of the green city concept has been very well developed in Banda Aceh city. This can be seen from the existing conditions, there are efforts made by the government towards eight categories of implementing green cities based on the Asian Green City Index (AGCI). But there are also some efforts that still need to be improved to be better, such as in the energy and CO2 category, the land use and building category and the water category.